341 Consenting Practices in Plastic Surgery. (28th February 2022) - Noton, T.; Benshetrit, G.; Bradley, A.; Mitchell, C.
Abstract: Introduction: Informed consent is a vital aspect of safe patient care within any surgical specialty, and if not completed thoroughly, may result in misinformation and patient dissatisfaction. Traditional paper consent forms are notoriously poorly completed by medical professionals, with common issues ranging from ineligible handwriting, to missing key components of the form. The aim of this audit was to assess our departments' compliance with standard trust consent forms and compare adherence to local and national consenting policies. Method: All elective and emergency plastic surgical procedures carried out over a one-week period from 17/05/2021 to 23/05/2021 were identified using eTrauma and Cerner operative records. In total, 40 procedures were identified. Consent forms were then reviewed and assessed for completion in key areas. 4 procedures were excluded due to the consent form not being available for review, and 1 procedure was excluded due to a cancellation. Results: The risks and benefits of procedures were generally documented to a high standard. Providing written information to patients, confirmation of consent if the procedure was being performed on a different day, and possible additional procedures were poorly completed throughout. 90% of consent forms screened, failed to include confirmation of the surgical site within the specific section of the form. Conclusions: Overall, the department demonstrated good compliance with completing trust consent forms. Electronic consent forms would likely address the shortcomings identified in this audit and should be adopted. Continued responsibility from the whole team should be highlighted and maintained to ensure a high standard of consenting.